The characteristics didactic gestures of a Study and Research Path involving mathematics and physics at secondary school - Gazzola Bascougnet, María Paz (2019)
This paper analyses the development of a Study and Research Path (SRP) involving mathematics and physics by means of the theoretical construct proposed by the Anthropological Theory of Didactics (ATD) called dialectics. The SRP was implemented in five secondary school math courses and 116 students participated in total. The data analysis was performed using qualitative techniques and constructing nominal variables and their modalities, which also allows the use of descriptive statistical techniques. In this work, absolute frequencies are analysed and some considerations are made - in the light of the theory - to interpret these results.